The Manuscript Versions of Shakespeare's Sonnet 2: A Reassessment. - RIBES TRAVER, PURIFICACIÓN (Scripta)
The present article focuses on the manuscript versions of Shakespeare's Sonnet 2 present in handwritten miscellanies from the second quarter of the Seventeenth century. A thorough reassessment of the textual nature of the high number of witnesses that have come down to us has been undertaken by newly transcribing and collating all the extant manuscripts, as well as revising the conclusions reached by previous editors and scholars on the presumable origin of these texts. The arguments posed by those who regard these manuscripts as early drafts of Shakespeare's 1609 Quarto, and the reasons alleged by those who contend that they are the product of the revision undertaken by educated compilers from the universities and the Inns of Court have been reviewed in the light of the new transcriptions and collations, that take their original spelling and punctuation into account, and look into the nature of their variant readings within the context of the different texts.